Rapid diagnosis of Japanese encephalitis by using an immunoglobulin M dot enzyme immunoassay. - Solomon, Tom; Thao, Le Thi Thu; Dung, Nguyen Minh; Kneen, Rachel; Hung, Nguyen The; Nisalak, Ananda; Vaughn, David W.; Farrar, Jeremy; Hien, Tran Tinh; White, Nicholas J.; Cardosa, Mary Jane (American Society for Microbiology, 1998)
Japanese encephalitis (JE) occurs in rural settings in southern and eastern Asia, where diagnostic facilities are limited. For the diagnosis of JE virus (JEV) infection, we developed a nitrocellulose membrane-based immunoglobulin M (IgM) capture dot enzyme immunoassay (MAC DOT) that is rapid, simple to use, requires no specialized equipment, and can distinguish JEV from dengue infection. In a prospective field study in southern Vietnam, 155 cerebrospinal fluid (CSF) and 341 serum samples were collected from 111 children and 83 adults with suspected encephalitis. The JEV MAC DOT, performed on site, was scored visually from negative to strongly positive by two observers, and the results were compared subsequently with those of the standard IgM capture enzyme-linked immunosorbent assay. For the 179 patients with adequate specimens, the MAC DOT correctly identified 59 of 60 JEV-positive patients and 118 of 119 JEV-negative patients (sensitivity [95% confidence intervals], 98.3% [92.1 to 99.9%]; specificity, 99.2% [95.9 to 100.0%]; positive predictive value, 0.98; negative predictive value, 0.99). The MAC DOT also correctly identified three patients with dengue encephalopathy. Admission specimens were positive for 73% of JE patients. Interobserver agreement for MAC DOT diagnosis was excellent (kappa 5 0.94). The JEV MAC DOT is a simple and reliable rapid diagnostic test for JE in rural hospitals.